A kind of preparation method of potassium hydroxide
By using metathesis reaction of lime milk and calcium oxide and composite hydrogel purification technology in the preparation process of potassium hydroxide, the problems of barium hydroxide and sodium ion impurities are solved, the purity and yield of potassium hydroxide are improved, and the Efficient preparation of potassium hydroxide.
Patent Information
- Application Number
- CN202411244869.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing potassium hydroxide preparation methods, barium hydroxide is expensive and leads to a decrease in purity, and there are sodium ion impurities, which affect the purity and yield of potassium hydroxide.
Lime milk and calcium oxide are used to generate hydrated calcium hydroxide in the metathesis step, and purify it through composite hydrogel. The sodium ions are removed by dynamic coordination and electrostatic adsorption to avoid the use of barium hydroxide.
The purity and yield of potassium hydroxide are improved, and the cost of raw materials is reduced. The mass purity of the prepared potassium hydroxide is 99.6-99.7%, and the yield is 94.5-96.1%, and it effectively removes sodium and calcium impurities.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of potassium hydroxide preparation, and in particular to a method for preparing potassium hydroxide. Background Art
[0002] Potassium hydroxide is a common inorganic base with strong alkalinity. It is soluble in water and ethanol and slightly soluble in ether. It easily absorbs moisture in the air and becomes deliquescent. It absorbs carbon dioxide and becomes potassium carbonate. It is mainly used as a raw material for the production of potassium salts and can also be used in electroplating, printing and dyeing, etc.
[0003] The existing methods for preparing potassium hydroxide mainly include electrolysis, potassium carbonate method and sodium hydroxide replacement method. Among them, the electrolysis method is to use potassium chloride solution as the electrolyte to perform electrolysis to generate potassium hydroxide; the potassium carbonate method is to use potassium carbonate as the raw material to react with sodium hydroxide to generate potassium hydroxide; the sodium hydroxide replacement method is to use sodium hydroxide as the raw material to react with potassium chloride to generate potassium hydroxide.
[0004] In addition to the above methods, the existing method for preparing potassium hydroxide also includes the potassium feldspar method. Potassium feldspar is composed of silicon dioxide, aluminum oxide, and potassium oxide. Potassium feldspar ore is a non-water-soluble potassium resource with a high potassium content, the widest distribution, and the largest reserves. The potassium feldspar method uses potassium feldspar as a raw material. When preparing potassium hydroxide, the commonly used method is: first, the potassium feldspar is crushed and ball-milled to obtain potassium feldspar powder; then potassium hydroxide is used to alkali-dissolve the potassium feldspar powder to obtain a solid phase product hexagonal potassium nephrite and a liquid phase product potassium silicate aqueous solution, and the liquid phase product potassium silicate aqueous solution is causticized with lime milk to generate a potassium hydroxide aqueous solution; then sulfuric acid is used to acid-dissolve the solid phase product hexagonal potassium nephrite, and the amount of sulfuric acid used during the acid dissolution process is controlled to ensure that only potassium ions are dissolved to obtain a potassium sulfate aqueous solution; then barium hydroxide is added to the potassium sulfate aqueous solution to perform a double decomposition reaction to generate a potassium hydroxide aqueous solution; finally, the generated potassium hydroxide aqueous solution is mixed, evaporated, concentrated, and dehydrated to obtain potassium hydroxide.
[0005] The method for preparing potassium hydroxide can improve the comprehensive utilization rate of potassium feldspar, and the yield of the prepared potassium hydroxide is high, but there are the following problems: first, the price of the barium hydroxide used is relatively high, which will increase the production cost of potassium hydroxide; second, in addition to silicon oxide, aluminum oxide and potassium oxide, potassium feldspar also contains sodium oxide, resulting in sodium ion impurities in the prepared potassium hydroxide, which further reduces the purity of the prepared potassium hydroxide.
[0006] In order to solve the above problems, the most commonly used method at present is: using calcium hydroxide instead of barium hydroxide, but the solubility of calcium sulfate in water is greater than that of barium sulfate in water, resulting in the introduction of calcium sulfate impurities into the prepared potassium hydroxide, further resulting in a decrease in the purity of the prepared potassium hydroxide, and because the solubility of calcium hydroxide in water itself is low, the generated calcium sulfate is also easy to cover the surface of calcium hydroxide, further affecting the dissolution of calcium hydroxide in water, resulting in incomplete reaction when calcium hydroxide and potassium sulfate react, further resulting in a decrease in the yield of the prepared potassium hydroxide; using anion exchange resin and cation exchange resin to purify potassium hydroxide, but the adsorption capacity of cation exchange resin for calcium ions is greater than that for sodium ions, and compared with potassium ions, sodium ions have a stronger hydration ability, resulting in a low removal rate of sodium ions by the cation exchange resin, further resulting in a decrease in the purity of the prepared potassium hydroxide. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a method for preparing potassium hydroxide, which can avoid the use of barium hydroxide and improve the purity and yield of potassium hydroxide.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing potassium hydroxide, comprising the following steps: crushing, ball milling, alkali dissolution, causticization, acid dissolution, double decomposition, evaporation concentration, and purification;
[0010] The crushing crushes the potassium feldspar to a particle size of 10-15 mm to obtain potassium feldspar particles;
[0011] The mass fraction of silicon dioxide in the potassium feldspar is 63.54%, the mass fraction of aluminum oxide is 17.94%, the mass fraction of potassium oxide is 16.40%, the mass fraction of iron oxide is 0.85%, and the mass fraction of sodium oxide is 1.10%;
[0012] The ball milling comprises adding potassium feldspar particles into a ball mill for ball milling to obtain potassium feldspar powder;
[0013] In the ball milling, the ball-to-material ratio is 4-5:1, the rotation speed is 150-200 rpm, and the time is 14-15 hours;
[0014] The alkali dissolution comprises mixing potassium feldspar powder, industrial-grade potassium hydroxide aqueous solution and deionized water, stirring at 260-280° C. at a stirring speed of 150-200 rpm for 60-70 minutes, cooling to 55-60° C., filtering to obtain an alkali-dissolved filter residue and an alkali-dissolved filtrate;
[0015] In the alkaline solution, the mass ratio of potassium feldspar powder, industrial-grade potassium hydroxide aqueous solution, and deionized water is 500:1000-1100:2500-2600;
[0016] The mass fraction of the industrial-grade potassium hydroxide aqueous solution is 50%;
[0017] The mass purity of the industrial-grade potassium hydroxide used in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0018] The causticizing comprises mixing the alkali-soluble filtrate and the lime milk, stirring at 90-95° C. and at a stirring speed of 300-350 rpm for 2.5-3 hours, filtering to obtain a causticized filtrate and a causticized filter residue, washing the causticized filter residue with hot deionized water, and mixing the washing liquid with the causticized filtrate to obtain a first portion of potassium hydroxide aqueous solution;
[0019] The mass ratio of the potassium feldspar powder in the alkali solution to the lime milk and hot deionized water in the causticizing process is 500:3800-4000:600-650;
[0020] In the causticizing, the mass fraction of the lime milk is 15%;
[0021] The temperature of the hot deionized water is 85-95°C;
[0022] The acid dissolution comprises mixing the alkali-soluble filter residue and concentrated sulfuric acid, stirring at 60-65° C. and at a stirring speed of 200-250 rpm for 1-1.5 hours, and filtering to obtain an acid-soluble filtrate and an acid-soluble filter residue;
[0023] The mass ratio of potassium feldspar powder in the alkali solution to concentrated sulfuric acid in the acid solution is 500:100-105;
[0024] In the acid dissolution, the mass fraction of the concentrated sulfuric acid is 98%;
[0025] The double decomposition comprises mixing the acid-dissolved filtrate and deionized water, stirring at room temperature at a stirring speed of 300-350 rpm for 20-30 minutes, then adding lime milk and calcium oxide simultaneously, continuing to stir for 10-15 minutes after the addition is completed, filtering to obtain a double decomposition filtrate and a double decomposition residue; and using the double decomposition filtrate as the second portion of potassium hydroxide aqueous solution;
[0026] The mass ratio of the potassium feldspar powder in the alkali solution to the deionized water, lime milk, and calcium oxide in the double decomposition is 500:2000-2100:550-600:40-45;
[0027] In the double decomposition, the mass fraction of the lime milk is 15%;
[0028] The lime milk and calcium oxide are added for 20-25 minutes.
[0029] The evaporation concentration comprises mixing the first potassium hydroxide aqueous solution and the second potassium hydroxide aqueous solution, and then evaporating and concentrating the mixture and dehydrating the mixture to obtain a crude potassium hydroxide product;
[0030] The purification comprises mixing the crude potassium hydroxide, deionized water and the composite hydrogel, stirring at room temperature at a stirring speed of 30-50 rpm for 10-15 minutes, filtering, taking the filtrate, centrifuging, taking the supernatant, passing it through an anion exchange resin and a cation exchange resin in sequence at a flow rate of 50-60 g / min, and then evaporating, concentrating and dehydrating to obtain potassium hydroxide;
[0031] The mass ratio of the potassium feldspar powder in the alkali solution to the deionized water and the composite hydrogel in the purification is 500:1400-1500:23-25;
[0032] In the purification, the anion exchange resin is a hydroxide anion exchange resin, which is a macroporous styrene-based weak base anion exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 7%;
[0033] The cation exchange resin is a potassium type cation exchange resin, which belongs to a macroporous styrene weak acid cation exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 6%;
[0034] The preparation method of the composite hydrogel comprises the following steps: adsorption, dissolution, cross-linking, and drying;
[0035] The adsorption comprises mixing the activated carbon and the potassium hydroxide aqueous solution, stirring at room temperature at a stirring speed of 100-150 rpm for 25-30 minutes, centrifuging, taking the precipitate, and drying it to obtain the adsorbed activated carbon;
[0036] In the adsorption, the mass ratio of activated carbon to potassium hydroxide aqueous solution is 9-10:280-300;
[0037] The mass concentration of the potassium hydroxide aqueous solution is 50%;
[0038] The particle size of the activated carbon is 10 μm;
[0039] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0040] The dissolving step comprises mixing polyvinyl alcohol 2499 and deionized water, and stirring the mixture at 85-90° C. and at a stirring speed of 100-150 rpm for 2-2.5 hours to obtain a polyvinyl alcohol aqueous solution;
[0041] In the dissolution, the mass ratio of polyvinyl alcohol 2499 to deionized water is 48-50:180-190;
[0042] The cross-linking comprises mixing a polyvinyl alcohol aqueous solution, adsorbed activated carbon and a potassium hydroxide aqueous solution, stirring at room temperature at a stirring speed of 100-150 rpm for 40-50 min, placing at -35°C to -30°C for 11-12 h, then placing at 15-20°C for 9-11 h, then placing at -35°C to -30°C for 11-12 h, and then placing at 15-20°C for 12-13 h to obtain a hydrogel;
[0043] In the cross-linking, the mass ratio of the polyvinyl alcohol aqueous solution, the adsorbed activated carbon, and the potassium hydroxide aqueous solution is 228-240:9-10:230-250;
[0044] The mass concentration of the potassium hydroxide aqueous solution is 1%;
[0045] The drying comprises freeze-drying the hydrogel, crushing the hydrogel to a particle size of 500-600 μm, and then soaking the mixture in a potassium hydroxide aqueous solution for 10-12 hours, filtering the mixture, and freeze-drying the mixture to obtain a composite hydrogel;
[0046] During the drying, the mass concentration of the potassium hydroxide aqueous solution is 50%.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] (1) The preparation method of potassium hydroxide of the present invention uses a combination of lime milk and calcium oxide in double decomposition. During the process of slowly adding lime milk and calcium oxide, calcium oxide reacts with water to generate hydrated calcium hydroxide, and releases heat to cause the reaction system to gradually heat up. The hydrated calcium hydroxide in the lime milk and the hydrated calcium hydroxide generated by the reaction of calcium oxide with water slowly dehydrate to generate small-particle calcium hydroxide during the gradual temperature rise. In addition, calcium oxide will also affect the hydrated calcium hydroxide in the lime milk during the reaction with water, promoting its dehydration to form small-particle calcium hydroxide, which then reacts with potassium sulfate in the acid-dissolved filtrate, thereby avoiding the problem of only adding lime milk. The hydrated calcium hydroxide in the lime milk needs to be dehydrated before reacting with potassium sulfate in the acid-dissolved filtrate. However, due to the slow dehydration, the dehydration can only be promoted by heating. However, during the heating process, a large amount of hydrated calcium hydroxide is rapidly dehydrated to form calcium hydroxide particles. After the calcium hydroxide particles react with sodium sulfate, the surface is coated with calcium sulfate, resulting in the calcium hydroxide particles being unable to fully participate in the reaction, further resulting in a problem of reduced yield. In addition, composite water is also used in the purification. Gel, in the preparation of the composite hydrogel, firstly, the activated carbon is mixed with the potassium hydroxide aqueous solution, after the activated carbon reaches the saturation of adsorption of potassium hydroxide, it is mixed with the polyvinyl alcohol aqueous solution, and then cross-linked with potassium hydroxide, and the polyvinyl alcohol completes the cross-linking in repeated freezing and thawing to form a polyvinyl alcohol hydrogel containing activated carbon, and then freeze-dried and crushed, and then soaked in a potassium hydroxide aqueous solution with a mass concentration of 50% to ensure that the crushed hydrogel reaches the saturation of adsorption of potassium hydroxide, and then freeze-dried to obtain the composite hydrogel; after the composite hydrogel is added to the potassium hydroxide crude aqueous solution, there is a dynamic coordination effect between the composite hydrogel and water and metal ions, and there is an electrostatic adsorption effect between the activated carbon and the metal ions. When the composite hydrogel is dynamically coordinated with water, the hydration of sodium ions and water is destroyed, thereby releasing sodium ions. Since the diameter of sodium ions is smaller than that of potassium ions, the electrostatic adsorption effect between sodium ions and activated carbon is stronger, so that the potassium ions adsorbed on the activated carbon can be replaced, the removal rate of sodium ions is improved, and the purity of the prepared potassium hydroxide is further improved;
[0049] (2) The method for preparing potassium hydroxide of the present invention uses industrial-grade potassium hydroxide for alkali dissolution during the preparation, and combined with the subsequent purification step, it can also achieve the purification of industrial-grade potassium hydroxide;
[0050] (3) The method for preparing potassium hydroxide of the present invention can avoid the use of barium hydroxide and reduce the cost of raw materials;
[0051] (4) The method for preparing potassium hydroxide of the present invention can improve the purity and yield of potassium hydroxide. The mass purity of the potassium hydroxide prepared by the present invention is 99.6-99.7%, the yield is 94.5-96.1%, the sodium content is 91-98 ppm, and the calcium content is 195-237 ppb. DETAILED DESCRIPTION
[0052] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.
[0053] The calculation formula for the yield of potassium hydroxide in Examples 1-3 and Comparative Examples 1-3 is: (mass of potassium hydroxide obtained × purity of potassium hydroxide obtained - mass of potassium hydroxide aqueous solution added in the alkali dissolution step in step 3 × 50% × 95.7%) / (500 × 16.40% × 2 × 56 / 94) × 100%.
[0054] Regarding the yield of potassium hydroxide, the composite hydrogel used in Examples 1-3 and Comparative Examples 1-2 also introduces potassium hydroxide through ion exchange, resulting in a larger yield of potassium hydroxide calculated according to the above formula. However, since the mass of potassium hydroxide introduced by the composite hydrogel cannot be detected, and considering that the mass of potassium hydroxide introduced by the composite hydrogel is small, the potassium hydroxide introduced by the composite hydrogel is not considered in the calculation formula for the yield of potassium hydroxide.
[0055] Example 1
[0056] A preparation method of potassium hydroxide, specifically:
[0057] 1. Crushing: crush the potassium feldspar to a particle size of 10 mm to obtain potassium feldspar particles;
[0058] The mass fraction of silicon dioxide in the potassium feldspar is 63.54%, the mass fraction of aluminum oxide is 17.94%, the mass fraction of potassium oxide is 16.40%, the mass fraction of iron oxide is 0.85%, and the mass fraction of sodium oxide is 1.10%;
[0059] 2. Ball milling: Add potassium feldspar particles into a ball mill for ball milling, control the ball-to-material ratio to be 4:1, the speed to be 150 rpm, the time to be 14 h, and obtain potassium feldspar powder;
[0060] 3. Alkali dissolution: 500 g of potassium feldspar powder, 1000 g of an industrial-grade potassium hydroxide aqueous solution with a mass fraction of 50%, and 2500 g of deionized water were mixed, stirred at 260°C at a stirring speed of 150 rpm for 60 min, cooled to 55°C, and filtered to obtain an alkali-soluble residue and an alkali-soluble filtrate;
[0061] The mass purity of the industrial-grade potassium hydroxide used in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0062] 4. Causticizing: the alkali-soluble filtrate obtained in step 3 and 3800 g of lime milk with a mass fraction of 15% are mixed, stirred at 90° C. and 300 rpm for 2.5 h, filtered to obtain a causticized filtrate and a causticized filter residue, and the causticized filter residue is washed with 600 g of deionized water at a temperature of 85° C., and the washing liquid is mixed with the causticized filtrate to obtain a first portion of potassium hydroxide aqueous solution;
[0063] 5. Acid dissolution: Mix the alkali-soluble residue obtained in step 3 with 100 g of concentrated sulfuric acid with a mass fraction of 98%, stir at 60° C. and 200 rpm for 1 h, and filter to obtain an acid-soluble filtrate and an acid-soluble residue;
[0064] 6. Double decomposition: after mixing the acid-dissolved filtrate and 2000 g of deionized water, stir at room temperature at a stirring speed of 300 rpm for 20 min, then slowly add 550 g of lime milk with a mass fraction of 15% and 40 g of calcium oxide at the same time, control the addition time of both to be 20 min, continue stirring for 10 min after the addition is completed, filter, and obtain a double decomposition filtrate and a double decomposition residue; the double decomposition filtrate is used as the second portion of potassium hydroxide aqueous solution;
[0065] 7. Evaporation and concentration: the first portion of the potassium hydroxide aqueous solution obtained in step 4 and the second portion of the potassium hydroxide aqueous solution obtained in step 6 are mixed, and then evaporated, concentrated and dehydrated to obtain a crude potassium hydroxide product;
[0066] 8. Purification: The crude potassium hydroxide obtained in step 7, 1400 g of deionized water, and 23 g of the composite hydrogel were mixed, stirred at room temperature at a stirring speed of 30 rpm for 10 min, filtered, the filtrate was taken, centrifuged, the supernatant was taken, passed through an anion exchange resin and a cation exchange resin in sequence at a flow rate of 50 g / min, evaporated, concentrated, and dehydrated to obtain potassium hydroxide;
[0067] The anion exchange resin is a hydroxide anion exchange resin, which is a macroporous styrene-based weak base anion exchange resin, with a resin particle size of 100 μm and a cross-linking degree of 7%;
[0068] The cation exchange resin is a potassium type cation exchange resin, which belongs to a macroporous styrene weak acid cation exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 6%;
[0069] The preparation method of the composite hydrogel is:
[0070] (1) Adsorption: 9 g of activated carbon and 280 g of a 50% potassium hydroxide aqueous solution were mixed, stirred at room temperature at a stirring speed of 100 rpm for 25 min, centrifuged, and the precipitate was taken and dried to obtain adsorbed activated carbon;
[0071] The particle size of the activated carbon is 10 μm;
[0072] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0073] (2) Dissolution: Mix 48 g of polyvinyl alcohol 2499 and 180 g of deionized water, and stir at 85° C. and 100 rpm for 2 h to obtain a polyvinyl alcohol aqueous solution;
[0074] (3) Cross-linking: 228 g of polyvinyl alcohol aqueous solution, 9 g of adsorbed activated carbon, and 230 g of 1% potassium hydroxide aqueous solution were mixed, stirred at room temperature at a stirring speed of 100 rpm for 40 min, allowed to stand at -35 ° C for 11 h, then allowed to stand at 15 ° C for 9 h, then allowed to stand at -35 ° C for 11 h, and then allowed to stand at 15 ° C for 12 h to obtain a hydrogel;
[0075] (4) Drying: freeze-drying the hydrogel, crushing it to a particle size of 500 μm, and then soaking it in a 50% potassium hydroxide aqueous solution for 10 h, filtering it, and freeze-drying it to obtain a composite hydrogel;
[0076] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%.
[0077] The potassium hydroxide obtained in this example is 573.7 g in total, with a purity of 99.6%, a yield of 95.1%, a sodium content of 94 ppm, and a calcium content of 237 ppb.
[0078] Example 2
[0079] A preparation method of potassium hydroxide, specifically:
[0080] 1. Crushing: crush the potassium feldspar to a particle size of 10 mm to obtain potassium feldspar particles;
[0081] The mass fraction of silicon dioxide in the potassium feldspar is 63.54%, the mass fraction of aluminum oxide is 17.94%, the mass fraction of potassium oxide is 16.40%, the mass fraction of iron oxide is 0.85%, and the mass fraction of sodium oxide is 1.10%;
[0082] 2. Ball milling: Add potassium feldspar particles into a ball mill for ball milling, control the ball-to-material ratio during ball milling to be 5:1, the speed to be 200 rpm, and the time to be 14.5 h to obtain potassium feldspar powder;
[0083] 3. Alkali dissolution: 500 g of potassium feldspar powder, 1050 g of an industrial-grade potassium hydroxide aqueous solution with a mass fraction of 50%, and 2550 g of deionized water were mixed, stirred at 270 ° C at a stirring speed of 200 rpm for 65 min, cooled to 55 ° C, and filtered to obtain an alkali-soluble residue and an alkali-soluble filtrate;
[0084] The mass purity of the industrial-grade potassium hydroxide used in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0085] 4. Causticizing: the alkali-soluble filtrate obtained in step 3 and 3900 g of lime milk with a mass fraction of 15% are mixed, stirred at 92° C. at a stirring speed of 330 rpm for 3 h, filtered to obtain a causticized filtrate and a causticized filter residue, and the causticized filter residue is washed with 620 g of deionized water at a temperature of 90° C., and the washing liquid is mixed with the causticized filtrate to obtain a first portion of potassium hydroxide aqueous solution;
[0086] 5. Acid dissolution: Mix the alkali-soluble residue obtained in step 3 with 102 g of concentrated sulfuric acid having a mass fraction of 98%, stir at 63° C. at a stirring speed of 220 rpm for 1 h, and filter to obtain an acid-soluble filtrate and an acid-soluble residue;
[0087] 6. Double decomposition: after mixing the acid-dissolved filtrate and 2050 g of deionized water, stir at room temperature at a stirring speed of 320 rpm for 25 min, then slowly add 570 g of lime milk with a mass fraction of 15% and 42 g of calcium oxide at the same time, control the addition time of both to be 22 min, continue stirring for 12 min after the addition is completed, filter, and obtain a double decomposition filtrate and a double decomposition residue; the double decomposition filtrate is used as the second portion of potassium hydroxide aqueous solution;
[0088] 7. Evaporation and concentration: the first portion of the potassium hydroxide aqueous solution obtained in step 4 and the second portion of the potassium hydroxide aqueous solution obtained in step 6 are mixed, and then evaporated, concentrated and dehydrated to obtain a crude potassium hydroxide product;
[0089] 8. Purification: The crude potassium hydroxide obtained in step 7, 1450 g of deionized water, and 24 g of the composite hydrogel were mixed, stirred at room temperature at a stirring speed of 40 rpm for 12 min, filtered, the filtrate was taken, centrifuged, the supernatant was taken, passed through an anion exchange resin and a cation exchange resin in sequence at a flow rate of 55 g / min, evaporated, concentrated, and dehydrated to obtain potassium hydroxide;
[0090] The anion exchange resin is a hydroxide anion exchange resin, which is a macroporous styrene-based weak base anion exchange resin, with a resin particle size of 100 μm and a cross-linking degree of 7%;
[0091] The cation exchange resin is a potassium type cation exchange resin, which belongs to a macroporous styrene weak acid cation exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 6%;
[0092] The preparation method of the composite hydrogel is:
[0093] (1) Adsorption: 9.5 g of activated carbon and 290 g of a 50% potassium hydroxide aqueous solution were mixed, stirred at room temperature at a stirring speed of 120 rpm for 28 min, centrifuged, and the precipitate was taken and dried to obtain adsorbed activated carbon;
[0094] The particle size of the activated carbon is 10 μm;
[0095] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0096] (2) Dissolution: Mix 49 g of polyvinyl alcohol 2499 and 185 g of deionized water, and stir at 87 °C at a stirring speed of 120 rpm for 2 h to obtain a polyvinyl alcohol aqueous solution;
[0097] (3) Cross-linking: 234 g of polyvinyl alcohol aqueous solution, 9.5 g of adsorbed activated carbon, and 240 g of 1% potassium hydroxide aqueous solution were mixed, stirred at room temperature at a stirring speed of 120 rpm for 45 min, allowed to stand at -30 ° C for 11.5 h, then allowed to stand at 18 ° C for 10 h, then allowed to stand at -30 ° C for 11.5 h, and then allowed to stand at 18 ° C for 12.5 h to obtain a hydrogel;
[0098] (4) Drying: freeze-drying the hydrogel, crushing it to a particle size of 500 μm, and then soaking it in a 50% potassium hydroxide aqueous solution for 11 hours, filtering it, and freeze-drying it to obtain a composite hydrogel;
[0099] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%.
[0100] The potassium hydroxide obtained in this example is 598.1 g in total, with a purity of 99.7%, a yield of 96.1%, a sodium content of 91 ppm, and a calcium content of 204 ppb.
[0101] Example 3
[0102] A preparation method of potassium hydroxide, specifically:
[0103] 1. Crushing: crush the potassium feldspar to a particle size of 15 mm to obtain potassium feldspar particles;
[0104] The mass fraction of silicon dioxide in the potassium feldspar is 63.54%, the mass fraction of aluminum oxide is 17.94%, the mass fraction of potassium oxide is 16.40%, the mass fraction of iron oxide is 0.85%, and the mass fraction of sodium oxide is 1.10%;
[0105] 2. Ball milling: Add potassium feldspar particles into a ball mill for ball milling, control the ball-to-material ratio during ball milling to be 5:1, the speed to be 200 rpm, and the time to be 15 h to obtain potassium feldspar powder;
[0106] 3. Alkali dissolution: 500 g of potassium feldspar powder, 1100 g of an industrial-grade potassium hydroxide aqueous solution with a mass fraction of 50%, and 2600 g of deionized water were mixed, stirred at 280°C at a stirring speed of 200 rpm for 70 min, cooled to 60°C, and filtered to obtain an alkali-soluble residue and an alkali-soluble filtrate;
[0107] The mass purity of the industrial-grade potassium hydroxide used in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0108] 4. Causticizing: the alkali-soluble filtrate obtained in step 3 and 4000 g of lime milk with a mass fraction of 15% are mixed, stirred at 95° C. at a stirring speed of 350 rpm for 3 h, filtered to obtain a causticized filtrate and a causticized filter residue, and the causticized filter residue is washed with 650 g of deionized water at a temperature of 95° C., and the washing liquid is mixed with the causticized filtrate to obtain a first portion of potassium hydroxide aqueous solution;
[0109] 5. Acid dissolution: Mix the alkali-soluble residue obtained in step 3 with 105 g of concentrated sulfuric acid having a mass fraction of 98%, stir at 65° C. and 250 rpm for 1.5 h, and filter to obtain an acid-soluble filtrate and an acid-soluble residue;
[0110] 6. Double decomposition: After mixing the acid-dissolved filtrate and 2100 g of deionized water, stir at room temperature at a stirring speed of 350 rpm for 30 min, then slowly add 600 g of lime milk with a mass fraction of 15% and 45 g of calcium oxide at the same time, and control the addition time of both to be 25 min. After the addition is completed, continue stirring for 15 min, filter, and obtain a double decomposition filtrate and a double decomposition residue; the double decomposition filtrate is used as the second portion of potassium hydroxide aqueous solution;
[0111] 7. Evaporation and concentration: the first portion of the potassium hydroxide aqueous solution obtained in step 4 and the second portion of the potassium hydroxide aqueous solution obtained in step 6 are mixed, and then evaporated, concentrated and dehydrated to obtain a crude potassium hydroxide product;
[0112] 8. Purification: The crude potassium hydroxide obtained in step 7, 1500 g of deionized water, and 25 g of the composite hydrogel were mixed, stirred at room temperature at a stirring speed of 50 rpm for 15 min, filtered, the filtrate was taken, centrifuged, the supernatant was taken, passed through an anion exchange resin and a cation exchange resin in sequence at a flow rate of 60 g / min, evaporated, concentrated, and dehydrated to obtain potassium hydroxide;
[0113] The anion exchange resin is a hydroxide anion exchange resin, which is a macroporous styrene-based weak base anion exchange resin, with a resin particle size of 100 μm and a cross-linking degree of 7%;
[0114] The cation exchange resin is a potassium type cation exchange resin, which belongs to a macroporous styrene weak acid cation exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 6%;
[0115] The preparation method of the composite hydrogel is:
[0116] (1) Adsorption: 10 g of activated carbon and 300 g of a 50% potassium hydroxide aqueous solution were mixed, stirred at room temperature at a stirring speed of 150 rpm for 30 min, centrifuged, and the precipitate was taken and dried to obtain adsorbed activated carbon;
[0117] The particle size of the activated carbon is 10 μm;
[0118] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%;
[0119] (2) Dissolution: Mix 50 g of polyvinyl alcohol 2499 and 190 g of deionized water, and stir at 90 °C and 150 rpm for 2.5 h to obtain a polyvinyl alcohol aqueous solution;
[0120] (3) Cross-linking: 240 g of polyvinyl alcohol aqueous solution, 10 g of adsorbed activated carbon, and 250 g of 1% potassium hydroxide aqueous solution were mixed, stirred at room temperature at a stirring speed of 150 rpm for 50 min, allowed to stand at -30 ° C for 12 h, then allowed to stand at 20 ° C for 11 h, then allowed to stand at -30 ° C for 12 h, and then allowed to stand at 20 ° C for 13 h to obtain a hydrogel;
[0121] (4) Drying: freeze-drying the hydrogel, crushing it to a particle size of 600 μm, and then soaking it in a 50% potassium hydroxide aqueous solution for 12 h, filtering it, and freeze-drying it to obtain a composite hydrogel;
[0122] The mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%.
[0123] The potassium hydroxide obtained in this example is 621.2 g in total, with a purity of 99.6%, a yield of 94.5%, a sodium content of 98 ppm, and a calcium content of 195 ppb.
[0124] Comparative Example 1
[0125] On the basis of the preparation method of potassium hydroxide in Example 2, the "570g of lime milk with a mass fraction of 15% and 42g of calcium oxide" in the sixth step of the double decomposition step is replaced by "326g of barium hydroxide", and the sixth step of the double decomposition step is specifically changed to:
[0126] The acid-dissolved filtrate and 2000 g of deionized water were mixed, stirred at room temperature at a stirring speed of 320 rpm for 25 min, and then 286 g of barium hydroxide was slowly added at the same time, and the addition time was controlled to be 22 min. After the addition was completed, stirring was continued for 12 min, and the mixture was filtered to obtain a double decomposition filtrate and a double decomposition residue; the double decomposition filtrate was used as the second portion of potassium hydroxide aqueous solution;
[0127] The potassium hydroxide obtained in this example is 598.2 g in total, with a purity of 99.7%, a yield of 96.2%, a sodium content of 86 ppm, and a calcium content of 180 ppb.
[0128] Comparative Example 2
[0129] On the basis of the preparation method of potassium hydroxide in Example 2, the "570 g of lime milk with a mass fraction of 15% and 42 g of calcium oxide" in the sixth step of the double decomposition step is replaced by "940 g of lime milk with a mass fraction of 15%", and the sixth step of the double decomposition step is specifically changed to:
[0130] The acid-dissolved filtrate and 2000 g of deionized water were mixed, and stirred at 92° C. at a stirring speed of 320 rpm for 25 min, and then 826 g of lime milk with a mass fraction of 15% was slowly added at the same time, and the adding time was controlled to be 22 min. After the addition was completed, stirring was continued for 12 min, and the mixture was filtered to obtain a double decomposition filtrate and a double decomposition residue; the double decomposition filtrate was used as the second portion of the potassium hydroxide aqueous solution;
[0131] The potassium hydroxide obtained in this example is 588.7 g in total, with a purity of 99.5%, a yield of 85.3%, a sodium content of 90 ppm, and a calcium content of 231 ppb.
[0132] Comparative Example 3
[0133] Based on the preparation method of potassium hydroxide in Example 2, the addition of 18 g of the composite hydrogel is omitted in the eighth purification step, and the eighth purification step is specifically changed to:
[0134] The crude potassium hydroxide obtained in step 7 and 1450 g of deionized water were mixed, stirred at room temperature at a stirring speed of 40 rpm for 12 min, passed through an anion exchange resin and a cation exchange resin in sequence at a flow rate of 55 g / min, and then evaporated, concentrated, and dehydrated to obtain potassium hydroxide;
[0135] The anion exchange resin is a hydroxide anion exchange resin, which is a macroporous styrene-based weak base anion exchange resin, with a resin particle size of 100 μm and a cross-linking degree of 7%;
[0136] The cation exchange resin is a potassium type cation exchange resin, which belongs to a macroporous styrene weak acid cation exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 6%;
[0137] The potassium hydroxide obtained in this embodiment is 603.7 g in total, with a purity of 98.5%, a yield of 94.4%, a sodium content of 0.7%, and a calcium content of 342 ppm.
[0138] Unless otherwise specified, all percentages used in the present invention are by mass.
[0139] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing potassium hydroxide, characterized in that: The process consists of the following steps: crushing, ball milling, alkali dissolution, causticization, acid dissolution, double decomposition, evaporation concentration, and purification; The causticizing comprises mixing the alkali-soluble filtrate and the lime milk, stirring at 90-95° C. for 2.5-3 hours, filtering to obtain a causticized filtrate and a causticized filter residue, washing the causticized filter residue with hot deionized water, and mixing the washing liquid with the causticized filtrate to obtain a first portion of potassium hydroxide aqueous solution; The double decomposition comprises mixing the acid solution filtrate obtained in the acid dissolution and deionized water, stirring for 20-30 minutes at room temperature, then adding lime milk and calcium oxide simultaneously, continuing to stir for 10-15 minutes after the addition is completed, filtering to obtain a double decomposition filtrate and a double decomposition residue; and using the double decomposition filtrate as the second portion of potassium hydroxide aqueous solution; The evaporation concentration comprises mixing the first potassium hydroxide aqueous solution and the second potassium hydroxide aqueous solution, and then evaporating and concentrating the mixture and dehydrating the mixture to obtain a crude potassium hydroxide product; The purification comprises mixing the crude potassium hydroxide obtained by evaporation and concentration, deionized water, and the composite hydrogel, stirring at room temperature for 10-15 minutes, filtering, taking the filtrate, centrifuging, taking the supernatant, passing it through an anion exchange resin and a cation exchange resin in sequence, and then evaporating and concentrating and dehydrating to obtain potassium hydroxide; The preparation method of the composite hydrogel comprises the following steps: adsorption, dissolution, cross-linking, and drying; For the adsorption, activated carbon and potassium hydroxide aqueous solution are mixed, stirred at room temperature for 25-30 minutes, centrifuged, and the precipitate is taken and dried to obtain adsorbed activated carbon; The dissolving step comprises mixing polyvinyl alcohol 2499 and deionized water, and stirring the mixture at 85-90° C. for 2-2.5 hours to obtain a polyvinyl alcohol aqueous solution; The cross-linking comprises mixing a polyvinyl alcohol aqueous solution, adsorbed activated carbon, and a potassium hydroxide aqueous solution, stirring the mixture at room temperature for 40-50 minutes, placing the mixture at -35°C to -30°C for 11-12 hours, then placing the mixture at 15-20°C for 9-11 hours, then placing the mixture at -35°C to -30°C for 11-12 hours, and then placing the mixture at 15-20°C for 12-13 hours to obtain a hydrogel; The drying comprises freeze-drying the hydrogel, crushing it, and then soaking it in a potassium hydroxide aqueous solution for 10-12 hours, filtering it, and freeze-drying it to obtain a composite hydrogel.
2. The method for preparing potassium hydroxide according to claim 1, wherein The crushing crushes the potassium feldspar to obtain potassium feldspar particles; The ball milling comprises adding potassium feldspar particles into a ball mill for ball milling to obtain potassium feldspar powder; In the ball milling, the ball-to-material ratio is 4-5:1, the rotation speed is 150-200 rpm, and the time is 14-15 hours.
3. The preparation method of potassium hydroxide according to claim 2, characterized in that The alkali dissolution comprises mixing potassium feldspar powder, industrial-grade potassium hydroxide aqueous solution and deionized water, stirring at 260-280° C. for 60-70 minutes, cooling to 55-60° C., filtering to obtain an alkali-dissolved filter residue and an alkali-dissolved filtrate; In the alkaline solution, the mass ratio of potassium feldspar powder, industrial-grade potassium hydroxide aqueous solution, and deionized water is 500:1000-1100:2500-2600; The mass fraction of the industrial-grade potassium hydroxide aqueous solution is 50%.
4. The method for preparing potassium hydroxide according to claim 3, wherein The mass ratio of the potassium feldspar powder in the alkali solution to the lime milk and hot deionized water in the causticizing process is 500:3800-4000:600-650; In the causticizing, the mass fraction of the lime milk is 15%; The temperature of the hot deionized water is 85-95°C.
5. The method for preparing potassium hydroxide according to claim 3, wherein The acid dissolution comprises mixing the alkali-soluble residue and concentrated sulfuric acid, stirring at 60-65° C. for 1-1.5 hours, and filtering to obtain an acid-soluble filtrate and an acid-soluble residue; The mass ratio of potassium feldspar powder in the alkali solution to concentrated sulfuric acid in the acid solution is 500:100-105; In the acid dissolution, the mass fraction of the concentrated sulfuric acid is 98%.
6. The method for preparing potassium hydroxide according to claim 3, wherein The mass ratio of the potassium feldspar powder in the alkali solution to the deionized water, lime milk, and calcium oxide in the double decomposition is 500:2000-2100:550-600:40-45; In the double decomposition, the mass fraction of the lime milk is 15%; The addition time of the lime milk and calcium oxide is 20-25 minutes.
7. The method for preparing potassium hydroxide according to claim 3, wherein The mass ratio of the potassium feldspar powder in the alkali solution to the deionized water and the composite hydrogel in the purification is 500:1400-1500:23-25; In the purification, the anion exchange resin is a hydroxide anion exchange resin, which is a macroporous styrene-based weak base anion exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 7%; The cation exchange resin is a potassium type cation exchange resin, which belongs to a macroporous styrene weak acid cation exchange resin, has a resin particle size of 100 μm, and a cross-linking degree of 6%; The flow rate through the anion exchange resin and the cation exchange resin is 50-60 g / min.
8. The method for preparing potassium hydroxide according to claim 3, wherein In the adsorption, the mass ratio of activated carbon to potassium hydroxide aqueous solution is 9-10:280-300; In the adsorption, the mass concentration of the potassium hydroxide aqueous solution is 50%; In the adsorption, the particle size of the activated carbon is 10 μm; In the alkaline solution, the mass purity of the industrial-grade potassium hydroxide in the industrial-grade potassium hydroxide aqueous solution is 95.7%; In the dissolution, the mass ratio of polyvinyl alcohol 2499 to deionized water is 48-50:180-190; In the cross-linking, the mass ratio of the polyvinyl alcohol aqueous solution, the adsorbed activated carbon, and the potassium hydroxide aqueous solution is 228-240:9-10:230-250; In the cross-linking, the mass concentration of the potassium hydroxide aqueous solution is 1%; During the drying, the mass concentration of the potassium hydroxide aqueous solution is 50%.
Citation Information
Patent Citations
Method for preparing potassium carbonate by adopting potash feldspar powder
CN103880044A
Method for preparing potassium sulphate and coproducing potassium hydroxide
CN104909389A